Teknik Marker Based Tracking Augmented Reality untuk Visualisasi Anatomi Organ Tubuh Manusia Berbasis Android - Ika Devi Perwitasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to learn the technique of Marker Based Tracking Augmented Reality which is implemented for Visualization of Anatomy of Human Body Organs. Augmented Reality Visualization Applications Anatomy of the Human Body Organ is built on the Android mobile platform device. In the analysis of the application interface design using the approach of User Center Design (UCD). Testing the application using Usability Test. Based on the results of implementation and testing, Marker Based AR technique successfully applied in making Visualization Applications Anatomy Human Body Organson Android Platform. Applications use markers to display digital content (2D images of the brain, eyes, heart, and lungs). The results of the Usability Test show users can see organ anatomy information very clearly and users are very interested in using the applications created because it provides a different experience in learning. Keywords : Augmented Reality, Marker Based Tracking, Human Organs, User Center Design